2012
DOI: 10.1136/thoraxjnl-2012-201747
|View full text |Cite
|
Sign up to set email alerts
|

Lung function is abnormal in 3-month-old infants with cystic fibrosis diagnosed by newborn screening

Abstract: Background Long-term benefits of newborn screening (NBS) for cystic fibrosis (CF) have been established with respect to nutritional status, but effects on pulmonary health remain unclear. Hypothesis With early diagnosis and commencement of standardised treatment, lung function at w3 months of age is normal in NBS infants with CF. Methods Lung clearance index (LCI) and functional residual capacity (FRC) using multiple breath washout (MBW), plethysmographic (pleth) FRC and forced expirations from raised lung vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
147
4
12

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 139 publications
(181 citation statements)
references
References 52 publications
(51 reference statements)
18
147
4
12
Order By: Relevance
“…Cross-sectional data in infants and children suggest that those with evidence of bacterial infection are more likely to have abnormal LCI (36,38,40). In a preschool crosssectional study, children who had "ever cultured" Pseudomonas aeruginosa from airway secretions had higher LCI than those who had not (32).…”
Section: Change In Lci With Microbiological Statusmentioning
confidence: 99%
See 2 more Smart Citations
“…Cross-sectional data in infants and children suggest that those with evidence of bacterial infection are more likely to have abnormal LCI (36,38,40). In a preschool crosssectional study, children who had "ever cultured" Pseudomonas aeruginosa from airway secretions had higher LCI than those who had not (32).…”
Section: Change In Lci With Microbiological Statusmentioning
confidence: 99%
“…In contrast to older groups, at least half of infants with CF have normal LCI (28,(40)(41)(42). Specifically, some infants appear to have normal LCI in the presence of abnormal infant spirometry (measured by the raised volume rapid thoracoabdominal compression technique) (40) or abnormal computed tomography (28).…”
Section: Observational Studies Lci Correlation With Other Pulmonary Pmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported that at 3 months, Forced Expired Volume in 0.5 seconds (FEV 0.5 ) was reduced in 25%(17/68) of infants while Lung Clearance Index (LCI) was elevated in 21%(15/70) [3]. ILF at 1yr was predicted by that at 3mth and impressively FEV 0.5 improved over the first year of life with standard UK treatment [4].…”
Section: Introductionmentioning
confidence: 98%
“…Entretanto, existem poucos dados relacionando o impacto do diagnóstico precoce nos desfechos clínicos e funcionais de crianças pré-escolares [5][6][7][8][9]. O objetivo deste estudo foi comparar os dados clínicos, laboratoriais e espirométricos de pacientes pré-escolares portadores de FC, entre o grupo cuja suspeita diagnóstica foi levantada a partir da pesquisa do IRT no TTN e o grupo…”
Section: Introductionunclassified